IMPROVING STUDENTS’ VOCABULARY MASTERY IN LEARNING ENGLISH USING CONTEXTUAL TEACHING AND LEARNING (CTL): A CLASSROOM ACTION RESEARCH OF THE FOURTH YEAR STUDENTS OF SD DJAMA’ATUL ICHWAN (DJI) SURAKARTA IN 2005/2006 ACADEMIC YEAR - SUGIARTI, SUGIARTI (2007)
This research is aimed to know whether or not the students have adequate vocabulary mastery in learning English, to know the student’s participation during English teaching learning process using CTL to improve students’ vocabulary mastery, and to describe the achievement of the students’ vocabulary mastery in their test result. The result of this study hopefully will give contribution in learning English. In this research, CTL is used to improve students’ vocabulary mastery in learning English using. This research was carried out at SD Djama’atul Ichwan, especially in class IV B that consists of 45 students. To collect the required data, the writer did observation, gave test, and used documentation. There were three cycles in this action research in which each cycle used pre-test and post-test. She analyzed the data by comparing the result of pre-test and post-test. The results of pre-test and post- test were used to know the score of the vocabulary mastery. The mean of the students` vocabulary mastery after the teacher did the action was 77.35 % that belongs to good category and the mean of the students` mean score was 77.27. While, before the teacher did the action, the mean of the students` vocabulary mastery was 45.06 % that belongs to fair category and the mean of the students` mean score was 45.17. Based on the research finding, it can be concluded that the result of the students` achievement showed that Contextual Teaching and Learning (CTL) in teaching vocabulary could improve the students’ participation and achievement better. The students’ score was getting better in each cycle. It indicated that the teaching learning process was successful in which both the researcher and the students gained the objectives. Therefore, it is better for the students to study English carefully through practice and experience, and to be active and creative in learning English. While the English teacher should teach the students with CTL, process considerable knowledge to manage an interesting classroom, and prepare the lessons they are going to teach as well as possible.